Iron and Steel : a Driving Guide to the Birmingham Area Industrial Heritage. - Bennett, James (Alabama, the forge of history., 2010)
This guidebook of historic iron-production sites is designed to give the reader a factual and illuminating look at the people and events that shaped Birmingham into one of America's leading steel centers. Iron & Steel is heavily illustrated with both color and historical black-and-white photographs. It can be used while visiting parks or read as a coherent volume before or after a visit. The book contains chapters devoted to the larger preserved sites open to the public, such as Sloss Furnaces National Historic Landmark and Tannehill Ironworks Historical State Park. It also highlights lesser-k.